Evaluación físico – química del aceite de chocho (Lupinus mutabilis) a partir de dos variedades de chocho (INIAP 450 Andino y Ecotipo local), dos solventes (éter de petróleo y hexano) por medio de extracción soxhlet, con dos estados de chocho (amargo y desamargado) en los Laboratorios Académicos de la Carrera de Ingeniería Agroindustrial de la Universidad Técnica de Cotopaxi en el periodo 2015 – 2016 - Arias Alvarez, July Nataly (2016)
This research is conducted in order to take advantage of the production lupine (Lupinus mutabilis), and get a derivative of this product, for which oil lupine was obtained, it said extraction is conducted in academic laboratories of the Career of Agroindustrial engineering at the Technical University of Cotopaxi. This product was obtained to give added value and a new choice of consumption of the grain; Applying the various factors under study it was determined by physical analysis - chemical treatment t5 (a2b1c1) for the variety of lupine local ecotype, solvents petroleum ether and state of bitter lupine is the best treatment which provided suitable ranges quality an edible oil such as pH (7,195), acid index (0.2000%), density (0.8650 g / ml) and temperature (24,45 °C); viscosity (53.5 cst), refracción index (1.470 to 20 ° C), saponification (188.06 mg KOH / g) Index: a physical – chemical analysis of the best treatment results are the following: ester (187.96 mg KOH / g), iodine (94.39 IG2 / 100 g), peroxide (0.00 meq O2 / Kg); microbiological analysis: mold count (<10 CFU)....